A Brief Introduction to Integrated Pest Management for Aquatic Systems. (20th September 2019) - Hubert, Terrance D.; Miller, James; Burkett, Dale
Abstract: Aquatic invasive plants and animals are increasingly becoming a problem, causing severe economic and ecological damage to critical freshwater systems. The best strategy for controlling an invasive pest employs an integrated pest management (IPM) approach using a combination of biological, physical, chemical, and social/cultural control methods. Here, we examine the history and development of IPM and provide a discussion of the components of an IPM program involving development, evaluation, and management. Control approaches will be reviewed and the application of this technique to aquatic systems will be discussed. A discussion of the Great Lakes Fishery Commission's (GLFC) Integrated Management of Sea Lamprey Petromyzon marinus Control Program will be provided to illustrate the application of IPM to an aquatic system.